Monoclonal Antibodies Directed to the Calcium-Free Conformation of Human Protein S - Marcovina, Santica; Coppola, Raffaella; Valsecchi, Carla; Zoppo, Adele; Gelfi, Cecilia; Mannucci, Pier Mannuccio (Thrombosis and Haemostasis, 1989)
Four mouse hybridomas secreting monoclonal antibodies specific for human protein S (PS) have been generated. The antibodies, all of the IgG1 subclass, were designated S2, S3, S8, and S10. In a fluid phase radioimmunoassay, the binding of monoclonal antibodies to PS was about 30% greater in the presence of EDTA and totally inhibited in presence of Ca2+. Using the same technique, we performed displacement curves of 125I-labeled PS by purified PS, thrombin-cleaved PS, normal plasma, plasma from a patient on warfarin therapy, and plasma from a patient with no free PS and only PS bound to C4b-binding protein. The slopes of the curves show that the monoclonal antibodies reacted equally with all the tested forms of PS indicating that the antigenic site(s) to which the monoclonal antibodies are directed are present and exposed in free and bound PS, in thrombin-cleaved PS, and in the coumarin form of the protein. Each EDTA-dependent antibody, immobilized on Sepharose 4B-CNBr was used to purify PS from the barium citrate-absorbed, ammonium sulphate-soluble fraction of plasma. The fraction eluted from the immunoabsorbent with a buffer containing 4 mmol/1 CaCl2 and analysed by SDS-PAGE, contained two bands, one migrating with conventionally purified PS and the other with purified C4b-binding protein. Homogeneous PS was obtained by chromatography of the barium citrate absorbate on a DEAE-Sephadex column. The protein peak containing the bulk of PS was subsequently applied to the immunoadsorbent and eluted with 4 mmol/1 CaCl2. These studies demonstrate that EDTA-dependent monoclonal antibodies can simplify the isolation of PS from human plasma.
Keywords: Protein S; Calcium-free conformation; Monoclonal antibodies